Diseño y construcción de un purificador de agua mediante radiación UV y cámara de electrodiálisis alimentado por energía solar fotovoltaica para usuario residencial de la ciudad de Yopal (Casanare). (2022)
The present project is directed towards the social character because, in the capital of the department of Casanare, Yopal there is a social problem which has been affecting the people of this city for several years, this difficulty is the lack of water supply drinking water among the population due to the lack of an aqueduct with the capacity to supply this essential liquid for human health, with the realization of this project it is sought to improve the quality of life and prevent diseases related to poor water quality, in the document it develops a small-scale water purifier (prototype) with the capacity to supply this drinkable liquid to a residential user of 5 people, in the development of the project a prototype is designed and built with the purpose of reducing microorganisms (Giarda and Cryptosporidium) through UV radiation artificially and the reduction of heavy metals (Nickel and Cadmium) by implementing from an electrodialysis chamber in the water, the water used by this system arrives with very low turbidity and no solid residues, this makes the prototype more effective.